4 As: A Discussion of How Institutions of Higher Education Respond to Incidents Related to Culture, Diversity, and Equity. (2nd July 2020) - Thornton, Natasha; Adams, Megan; Bennett, Ann; Myers, Marrielle; Ritchie, Scott; Rodriguez, Sanjuana
Abstract : In this article, we offer an analysis of how institutions of higher education have responded to occurrences related to racism in educational contexts and the larger society. Since the initial drafting of this manuscript, continued police brutality and racially motivated tragedies have prompted protests and uprising across the US and the world, specifically after the killings of Ahmaud Arbery in Georgia, Breona Taylor in Kentucky, and George Floyd in Minnesota. This social unrest reflects the ways in which people respond when enough is enough. In addition, a number of schools across the P-20 landscape are engaging in discussions around equity and racism and responding in ways that address racist systems and policies. We conclude this article with a discussion of what institutions of higher education should aspire to in order to humanize the educational contexts for a more equitable and anti-racist society. We hope this discussion around past incidents provide a lens of possibilities for meaningful change; because as we knew when writing the initial draft, and as we still know, lives depend on it.